The Effect of Augmented Reality on Glasses Purchasing Decisions Using the Structural Equation Model Method - Ilham Prabowo; M. Fakhriza; Muhammad Dedi Irawan (Universitas Medan Area, 2023)
Development of information technology in the business sector can be seen with many business people marketing the sale of their services or products by utilizing social media platforms and also e-commerce because it can make it easier for buyers to get the desired information anywhere and anytime. The optimization of social media and e-commerce has been implemented by Fifan Glasses Store to sell their products. Generally, buyers will try on the frames one by one until they decide to buy them. But, online buyers cannot try on the frames and can only see the frames based on the pictures in the catalog provided by Fifan Glasses Store. For this reason, an Android-based Augmented Reality eyeglass frame application will be built at Fifan Glasses Store. The purpose of building this application is to facilitate online buyers in trying on the frames that have been provided and minimize the occurrence of damage to eyeglass frames by prospective buyers. This research uses the Rapid Application Development (RAD) method in building the application and this research will also analyze the effect of the application of Augmented Reality glasses frames using the Structural Equation Model (SEM) method. The final results of the analysis of the effect of Augmented Reality on eyeglass frames by testing the outermodel, inner model, and hypothesis show that Augmented Reality has a positive effect on purchasing decisions for glasses at Fifan Glasses Store.